Health Safety of Soft Drinks: Contents, Containers, and Microorganisms. (28th January 2015) - Kregiel, Dorota
Abstract : Soft drinks consumption is still a controversial issue for public health and public policy. Over the years, numerous studies have been conducted into the possible links between soft drink intake and medical problems, the results of which, however, remain highly contested. Nevertheless, as a result, increasing emphasis is being placed on the health properties of soft drinks, by both the industry and the consumers, for example, in the expanding area of functional drinks. Extensive legislation has been put in place to ensure that soft drinks manufacturers conform to established national and international standards. Consumers trust that the soft drinks they buy are safe and their quality is guaranteed. They also expect to be provided with information that can help them to make informed decisions about the purchase of products and that the information on product labels is not false or misleading. This paper provides a broad overview of available scientific knowledge and cites numerous studies on various aspects of soft drinks and their implications for health safety. Particular attention is given to ingredients, including artificial flavorings, colorings, and preservatives and to the lesser known risks of microbiological and chemical contamination during processing and storage.